Online Guarantee System With Soma Methods - Fauzan Akbar Rosyadi; Ahmad Nurul Fajar (Jurnal Indonesia Sosial Teknologi, 2024)
Web service-based applications are applications that use Restful to exchange data over the network and interact directly with other applications. One of the advantages of web service-based applications is that many applications can access services on different platforms. This is very beneficial in the business sector if a company or organization builds applications on a large scale, and application development is carried out in stages. With the characteristics of web service-based applications, namely a neutral platform, it is very easy to integrate systems when the development process is carried out in stages. Therefore, this research will design a web service-based application based on business processes, especially Kredit Usaha Rakyat (KUR) between PT ABC Credit Guarantee Company and PT Bank XYZ. The methods used are Thomas Erl's SOA methods and SOMA. The results obtained are a method that will be a guide for producing web service-based KUR Online Guarantee applications with PT Bank XYZ.